Minimal residual disease by flow cytometry and allelic‐specific oligonucleotide real‐time quantitative polymerase chain reaction in patients with myeloma receiving lenalidomide maintenance: A pooled analysis. Issue 5 (18th December 2018) - Gambella, Manuela; Omedé, Paola; Spada, Stefano; Muccio, Vittorio Emanuele; Gilestro, Milena; Saraci, Elona; Grammatico, Sara; Larocca, Alessandra; Conticello, Concetta; Bernardini, Annalisa; Gamberi, Barbara; Troia, Rossella; et al.
Abstract : Background: Minimal residual disease (MRD) is one of the most relevant prognostic factors in patients with multiple myeloma (MM); however, the impact of maintenance therapy on MRD levels remains unclear. Among patients with newly diagnosed MM (NDMM) who received lenalidomide maintenance until they developed disease progression, the role of MRD status as a predictor of progression‐free survival (PFS) was evaluated by multiparameter flow cytometry (MFC) and allelic‐specific oligonucleotide real‐time quantitative polymerase chain reaction (ASO‐RQ‐PCR) analysis. Methods: Seventy‐three patients with NDMM enrolled in the RV‐MM‐EMN‐441 (clinical trials.gov identifier, NCT01091831) and RV‐MM‐COOP‐0556 (clinicaltrials.gov identifier, NCT01208766; European Myeloma Network EMN02/HO95 MM Trial) phase 3 trials who achieved at least a very good partial response after intensification/consolidation were included. The median patient age was 57 years (interquartile range, 53‐61 years), and all patients received lenalidomide maintenance until they developed progression. MRD was evaluated on bone marrow after intensification/consolidation, after 6 courses of maintenance, and every 6 months thereafter until clinical relapse using both ASO‐RQ‐PCR (sensitivity, 10 −5 ) and MFC (sensitivity, from 10 −4 to 10 −5 ). Results: After intensification/consolidation, 33 of 72 patients (46%) achieved a molecular complete response (m‐CR), and 44 of 70 (63%) achieved a flow complete response (flow‐CR). Almost 27% of patients who were MRD‐positive after consolidation became MRD‐negative during maintenance. After a median follow‐up of 38 months, PFS was prolonged in patients who achieved negative MRD status during maintenance according to results from both ASO‐RQ‐PCR analysis (hazard ratio, 0.29; 95% confidence interval, 0.14‐0.62; P = .0013) and MFC (hazard ratio, 0.19; 95% confidence interval, 0.09‐0.41; P < .001). The impact of negative MRD status on PFS was similar in all subgroups (ASCT and no‐ASCT; International Staging System stages I, II, and III; high‐risk and standard‐risk cytogenetics), and the two techniques were highly correlated. Conclusions: MRD status is a stronger predictor of PFS than standard risk factors, and lenalidomide maintenance further increases the rate of negative MRD results. Abstract : Among patients with myeloma, the ability to achieve negative minimal residual disease status is enhanced by maintenance treatment with lenalidomide. An assessment of minimal residual disease using molecular and immunophenotypic assays is an optimal prognosticator in patients who have newly diagnosed multiple myeloma.